2022
DOI: 10.1186/s13063-022-06923-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of an internet-based self-guided hand exercise program to improve hand function in people with systemic sclerosis: the Scleroderma Patient-centered Intervention Network Hand Exercise Program (SPIN-HAND) trial

Abstract: Background Systemic sclerosis (scleroderma; SSc) is a rare autoimmune connective tissue disease. Functional impairment of hands is common. The Scleroderma Patient-centered Intervention Network (SPIN)-HAND trial compared effects of offering access to an online self-guided hand exercise program to usual care on hand function (primary) and functional health outcomes (secondary) in people with SSc with at least mild hand function limitations. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Kwakkenbos [30] conducted a study where for a standardized mean difference of 0.25, 5% level of significance, 80% power, and 10% loss to follow-up, a minimum of 586 participants were required to conduct the study. There was no clarity on whether 586 in each group is required, as reproducing the said sample size resulted in 279 in each group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kwakkenbos [30] conducted a study where for a standardized mean difference of 0.25, 5% level of significance, 80% power, and 10% loss to follow-up, a minimum of 586 participants were required to conduct the study. There was no clarity on whether 586 in each group is required, as reproducing the said sample size resulted in 279 in each group.…”
Section: Resultsmentioning
confidence: 99%
“…Dupuis [29] and Pielkenrood [31] provided no information regarding blinding. Kwakkenbos [30] blinded the statistical analysts to trial arm allocation, but were again unblinded for the complier effect analyses, which required the knowledge of intervention arm consent. Fahim [32] blinded the investigators who performed the analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome data at 3 and 6 months showed that CHFS did not differ significantly between patients undergoing SPIN-HAND and those who did not receive any online support, nor did the PROs analysed. The scarce success of this kind of intervention could be due to the method of enrolment and to the lack of guidance of a health professional (65).…”
Section: Patient-reported Outcomesmentioning
confidence: 99%